Use of Augmented Reality in the Teaching-Learning of Natural Science (2018)
Introduction: The article derives from the research “Use of augmented reality in the teaching-learning of natural science” conducted in 2016 and the first half of 2017 at the School of Computer Systems Engineering, Universidad Tecnológica de Panamá.Problem: Currently, Panama does not offer technological solutions in the educational field that support the process of teaching-learning about natural areas and their conservation.Aim: To contribute to improving the process of teaching-learning natural science and the conservation of the environment through mobile devices and augmented reality.Methods: Research-action was used, for which the work to be done was planned, the application was developed, students using the application were then observed, and the results were presented according to the observations and a rubric applied to students.Results: An application with augmented reality was developed to support the process of teaching-learning natural science and, in this case, the teaching and conservation of natural areas.Conclusion: We have managed to create animations that allow students to take in the information of natural areas and thus strengthen their learning through interactive contents.Originality: So far, the implementation of this type of applications in rural schools had not been addressed from this perspective. The project has enabled the academic community to have a valuable application to teach about the conservation of natural areas.Limitations: The project only covers the learning and conservation of natural areas.